Benign abducens nerve palsy: diagnosis by exclusion - U., Praveen; Save, Sushma; Singh, Sanjay (International Journal of Contemporary Pediatrics, 2019)
Of all the cranial nerves, the abducens nerve has the longest intracranial course hence is most common cranial nerve to be affected secondary to any potentially devastating intracranial cause. It can indicate significant underlying pathology. Abducens or sixth cranial nerve innervates lateral rectus muscle and pathology of this nerve results in abduction deficiency of ipsilateral eye. Most of the time it will be unilateral but bilateral involvement is also well known. It can recurrent without any underlying identifiable pathology. The 6th nerve palsy is considered as benign after ruling out all possible causes. Benign causes account for just 9 to 14% of all 6th nerve palsies in children. Most of the time benign 6th nerve palsy occurs after viral infection or vaccination as an immunological reaction. In our case patient had history of pentavalent vaccination 1 month back. After thorough investigation and ruling out all possible causes it was attributed to post vaccination immunological reaction. which resolved spontaneously over 4months.